Letter - Lewisham Trades Council and Borough Labour Party, 11 May 1926 (1) (Lewisham)
1926-05-11 "Letter - Lewisham Trades Council and Borough Labour Party, 11 May 1926 (1)" [g0211001.jpg], 11 May 1926 Local Organisation